Ambientes de aprendizaje y su incidencia en el proceso académico del área de lengua y literatura en los estudiantes de 3er año de EGB de la Unidad Educativa Víctor Mercante, 2023-2024 - Morales Carriel, Ruth Aracely (2023)
Learning environments are spaces created in the classroom, with the objective of facilitating the academic process since they allow the acquisition of new knowledge and skills. These places are not restricted only to school classrooms; they include a variety of locations and contexts, ranging from classrooms to virtual environments, museums, libraries, work environments and recreational corners. Therefore, the main objective of this case study is to determine the incidence of learning environments in the academic process of the area of Language and Literature in the 3rd year EGB students of the “Víctor Mercante” Educational Unit, 2023-2024. The methodology of this case study has a qualitative approach; While the research was descriptive, field and explanatory, inductive and deductive methods were also used, the population and sample are represented by 35 students and the tutor teacher of the 3rd year parallel "A" belonging to the Victor Mercante Educational Unit, it is It is important to mention that to obtain relevant information on the topic, two techniques were used: direct observation, directed at the students, and an interview with the teacher. The results obtained were that learning environments in the area of Language and Literature face difficulties and challenges, such as the scarcity of teaching materials, the lack of motivating environments, and rigidity in teaching. Therefore, it is concluded that the learning environments in this subject are not effective and do not allow meaningful learning for students.